2018
DOI: 10.1136/bmjgh-2017-000639
|View full text |Cite
|
Sign up to set email alerts
|

Verbal autopsy in health policy and systems: a literature review

Abstract: IntroductionEstimates suggest that one in two deaths go unrecorded globally every year in terms of medical causes, with the majority occurring in low and middle-income countries (LMICs). This can be related to low investment in civil registration and vital statistics (CRVS) systems. Verbal autopsy (VA) is a method that enables identification of cause of death where no other routine systems are in place and where many people die at home. Considering the utility of VA as a pragmatic, interim solution to the lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 42 publications
2
65
0
1
Order By: Relevance
“…Hence, facility level IDSR reports may not be sufficiently timely to pick up the outbreaks from community. The strengthened community level surveillance and verbal autopsy to detect unusual deaths can be a good approach to detect lower level health events and provide timely response [30]. By the fact of traditional medicine health seeking behaviour among villagers in Malawi, it is also important to understand how these behaviours may delayed the outbreak detection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, facility level IDSR reports may not be sufficiently timely to pick up the outbreaks from community. The strengthened community level surveillance and verbal autopsy to detect unusual deaths can be a good approach to detect lower level health events and provide timely response [30]. By the fact of traditional medicine health seeking behaviour among villagers in Malawi, it is also important to understand how these behaviours may delayed the outbreak detection.…”
Section: Discussionmentioning
confidence: 99%
“…Facility level IDSR reports may not be sufficiently timely to pick up the outbreaks from community. The strengthened community level surveillance and verbal autopsy to detect unusual deaths can be a good approach to detect lower level health events and provide timely response [26]. In Malawi, a pilot study conducted in Lilongwe District in Central Region showed that mobile technologies had good opportunities to improve timeliness of HMIS reports [27].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure adopted in community epidemiology over the years with the same criteria for all events, independently of the underlying or suspected cause and/or disease, involves formal reporting such as a "verbal autopsy." The collective context-oriented interpretation of this technique of event qualification is increasingly recognized [18]. Training promoters to collect, report, judge, and verify cases, basing their narratives on facts, in regular dialog with a professional provides strong backing for their responsibility and accuracy in pursuing what is most likely and plausible and/ or needs confirmation.…”
Section: Lowmentioning
confidence: 99%